2016
DOI: 10.1160/th16-02-0117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high or low protamine dosing on postoperative bleeding following heparin anticoagulation in cardiac surgery

Abstract: While experimental data state that protamine exerts intrinsic anticoagulation effects, protamine is still frequently overdosed for heparin neutralisation during cardiac surgery with cardiopulmonary bypass (CPB). Since comparative studies are lacking, we assessed the influence of two protamine-to-heparin dosing ratios on perioperative haemostasis and bleeding, and hypothesised that protamine overdosing impairs the coagulation status following cardiac surgery. In this open-label, multicentre, single-blinded, ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 38 publications
0
39
1
1
Order By: Relevance
“…165 In a second RCT, a protamine-to-heparin dosing ratio of 1.3 over the total heparin dose was associated with significantly more postoperative bleeding (615 ml, 95% CI 500-830 vs 470 ml, 95% CI 420-530; P ¼ 0.02) compared with a dosing ratio of 0.8, whereas post-protamine ACT levels were comparable among the groups. 154 None of the patients showed signs of heparin rebound. A recent RCT in patients having CABG showed that a protamine-to-heparin dosing ratio o0.6 was associated with significantly more blood loss within 12 h after surgery [420 ml (interquartile range 337-605 ml) vs 345 ml (interquartile range 230-482 ml); P ¼ 0.0041], but no difference in PRBC transfusion was noted (2.3 units vs 2.7 units; P ¼ 0.83) compared to patients subjected to a ratio 40.8.…”
Section: Protaminementioning
confidence: 92%
“…165 In a second RCT, a protamine-to-heparin dosing ratio of 1.3 over the total heparin dose was associated with significantly more postoperative bleeding (615 ml, 95% CI 500-830 vs 470 ml, 95% CI 420-530; P ¼ 0.02) compared with a dosing ratio of 0.8, whereas post-protamine ACT levels were comparable among the groups. 154 None of the patients showed signs of heparin rebound. A recent RCT in patients having CABG showed that a protamine-to-heparin dosing ratio o0.6 was associated with significantly more blood loss within 12 h after surgery [420 ml (interquartile range 337-605 ml) vs 345 ml (interquartile range 230-482 ml); P ¼ 0.0041], but no difference in PRBC transfusion was noted (2.3 units vs 2.7 units; P ¼ 0.83) compared to patients subjected to a ratio 40.8.…”
Section: Protaminementioning
confidence: 92%
“…Therefore, a 1 : 1 ratio between primary heparin dose and protamine dose cannot be recommended. Here, a heparin to protamine ratio of 1 : 0.6-0.8 seems to be more effective [56,61,62]. Additional protamine administration is definitively not beneficial in patients with a prolonged ACT due to a protamine overdose.…”
Section: Korean J Anesthesiolmentioning
confidence: 98%
“…4 Algorithms for ROTEM-guided management CT IN /CT HEP -ratio ≤ 1, but also with a significant and long-acting inhibition of platelet function including the adenosine diphosphate (ADP)-and thrombin receptor-activating peptide (TRAP)-pathway [57][58][59][60]. RCTs confirmed that a protamine overdose is associated with a significant increase in blood loss, transfusion requirements, and need for re-surgery after cardiac surgery [61,62]. Therefore, a 1 : 1 ratio between primary heparin dose and protamine dose cannot be recommended.…”
Section: Korean J Anesthesiolmentioning
confidence: 99%
“…Obviously, while the former reading suggests a more than sufficient degree of heparin anticoagulation, the latter clearly is far below our target value of 430 seconds for CPB and, if true, would have put the patient at risk for clot formation within the CPB circuit. In fact, it is not far fetched that some of the reported CPB cases of intracardiac and oxygenator thrombosis [18][19][20][21] may be due to wrong ACT measurements.…”
Section: Discussionmentioning
confidence: 99%